PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RSUD EMBUNG FATIMAH - CLARA CONI CONSTANTYA BR GINTING; HENDRI HERMAN (LP2MTBM MAKARIOZ, 2020)
This study focuses on issues regarding facilities at Embung Fatimah Regional Hospital and the quality of services availableat Embung Fatimah Regional Hospital. with the aim to test the extent of the role of facilities and service quality can improvepatient satisfaction at Embung Fatimah Regional Hospital. The research method used is quantitative research by looking forcausal associative relationships. with a population of 257 patients. The formula used to determine the number of samples isthe Slovin formula, with an error rate of 0.05 or 5% with a total of 156 samples. Data collection through a questionnaire wascarried out at Embung Fatimah District Hospital with the help of the SPSS Version 25 calculation program. The results ofthe coefficient of determination (R2) showed that the effect of facilities and service quality was 37.7% on customersatisfaction. The conclusion of this study is that the facility partially has a positive and significant effect on customersatisfaction, so the quality of service partially has a positive and significant effect on patient satisfaction and simultaneouslythe facility and service quality has a significant effect on patient satisfaction.